"Jetzt machen wir hier mal Multikulti": Fostering Critical Engagement with Multiculturalism through Peer-Assisted Language Learning - Schallié, Charlotte; Thorson, Helga (Die Unterrichtspraxis, 2012)
In this article we present an integrated curricular model for addressing the transition from the intermediate to the advanced language level through peer‐assisted learning activities in the post‐secondary German classroom. In a series of group projects between students in second‐ and third‐year conversation courses, we employed a learner‐centered approach that encouraged reciprocal peer mentoring. Both the contemporary focus on multiculturalism and the format involving collaborative work between students in two different language courses were critical components of our project. Engaging with contemporary political and cultural discourses in a peer‐assisted learning environment, course participants obtained important skill sets, which served to enrich their linguistic, cultural, cognitive, and interpersonal competencies.